Digital telemedicine interventions for patients with multimorbidity: a systematic review and meta-analysis. Issue 10 (13th October 2020) - Kraef, Christian; van der Meirschen, Marc; Free, Caroline
Abstract : Objective: To determine the effectiveness of digital telemedicine interventions designed to improve outcomes in patients with multimorbidity. Design: Systematic review and meta-analysis of available literature. Data sources: MEDLINE, EMBASE, The Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and the Database of Abstracts of Reviews of Effectiveness and hand searching. The search included articles from inception to 19 April 2019 without language restrictions. The search was updated on 7 June 2020 without additional findings. Eligibility criteria: Prospective interventional studies reporting multimorbid participants employing interventions with at least one digital telemedicine component were included. Primary outcomes were patient physical or mental health outcomes, health-related quality of life scores and the utilisation of health services. Results: Out of 5865 studies initially identified, 7 articles, reporting on 6 studies were retained (total of 699 participants). Four of these studies reported interventions including integration with usual care, two studies had interventions with no links to usual patient care. Follow-up periods lasted between 2 and 6 months. Among the studies with links to usual care, the primary outcomes were systolic blood pressure (SBP) (three studies), haemoglobin A1c (HbA1c) (three studies), total cholesterol (two studies) and self-perceived health status (one study). The evidence ranged from very low to moderate certainty. Meta-analysis showed a moderate decrease in SBP (8 mm Hg (95% CI 4.6 to 11.4)), a small to moderate decrease in HbA1c (0.46 mg/dL (95% CI 0.25 to 0.67)) and moderate decrease in total cholesterol (cholesterol 16.5 mg/dL (95% CI 8.1 to 25.0)) in the intervention groups. There was an absence of evidence for self-perceived health status. Among the studies with no links to usual care, time to hospitalisation (median time to hospitalisation 113.4 days intervention and 104.7 days control group, absolute difference 12.7 days) and the Minnesota Living with Heart Failure Questionnaire (intervention group 35.2 score points, control group 23.9 points, absolute difference 11.3, 95% CI 5.5 to 17.1) showed small reductions. The Personal Health Questionnaire (PHQ-8) showed no evidence of improvement (intervention 7.6 points, control 8.6 points, difference 1.0 points, 95% CI −22.9% to 11.9%). Conclusion: Digital telemedicine interventions provided moderate evidence of improvements in measures of disease control but little evidence and no demonstrated benefits on health status. Further research is needed with clear descriptions of conditions, interventions and outcomes based on patients' and healthcare providers' preferences. PROSPERO registration number: CRD42019134872.